(3GdUaGJs - (3GdfVQ Hf Tejd Hf NQTI Hf jRjO GdeGRfj GdJejej, CHh GdMSf,J (B203 (3g` s
(3ChdgG (B:s
(3hbGd (B: (3hcd TF ef GdOfjG aLYJ Hg ZjQ GHf YUe hEf YPHJfi Ldd Ci UZjQ s
(3BNQgG (B:s
(3gPG BNQ cJGH GdBHGQ hGdQcGjG hGdMjGV hGdOdGA hGdCQTjI hUaI GdNeQ s
(3GdeNWhW YHGQI Yf (B:s
(3GdhQbI GdCNjQI ef GdHGH GdQGHY efg hgh ai GdBHGQ hGdQcGjG hGdMjGV hGdOdGA hGdCQTjI hUaI GdNeQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B33s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdChd (B- (3bSe GdKGfi (B- (3U (B142 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GddZIs